A Novel Empirical Fractional Approach for Modeling the Clogging of Membrane Filtration During Protein Microfiltration - Leila Cherifi; Yamina Ammi; Salah Hanini; Mohamed Hentabli; Ouafa Belkacem; Jérôme Harmand (Membranes)
This study addresses the pervasive challenge of membrane filtration clogging across various industries. Eight new empirical fractional models are proposed based on the volume accumulation change curve. The effectiveness of these models in predicting material accumulation and characterizing clogging patterns is evaluated. The models are validated against experimental data, achieving impressive coefficients of determination (R2) between 0.9896 and 0.9997 and relative root mean squared errors (nRMSE) ranging from 0.8674% to 2.9548%. Furthermore, comparing the results with theoretical models of Hermia allows us to relate the empirical models to clogging mechanisms.